POLA PENCARIAN INFORMASI SISWA SEKOLAH MENENGAH PERTAMA PASCA ADAPTASI PEMBELAJARAN JARAK-JAUH - Alwan Husni Ramdani; Haria Saputry Wahyuni; Gustiana Sabarina (Nusantara Journal of Information and Library Studies (N-JILS), 2022)
As time goes by, the policy for the Implementation of Community Activity Restrictions (PPKM) has begun to loosen along with the start of face-to-face learning activities in schools. The transition from distance learning to face-to-face learning has brought significant changes to junior high school students in terms of how they access the information they need related to learning. This study tries to examine the pattern of student information seeking during the transition period. This research is qualitative research with observations and interviews with students of SMPN 1 Cibatu Kab. Garut. The research findings indicate that the information search pattern based on David Ellis' information search model, only 3 processes are passed by students namely starting, chaining, browsing. Changes in the habitual pattern of seeking information through internet-based search engines make students not carry out an in-depth search for information. The transition from distance learning to face-to-face learning implies that internet-based information sources are the main source for meeting information needs in the educational environment. Future research will focus on the effectiveness of using search engines as a means of student learning.Keywords: information literacy, information search patterns. face-to-face learningABSTRAKSeiring berjalannya waktu kebijakan Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) yang mulai melonggar beriringan dengan kegiatan mulainya aktifitas pembelajaran tatap muka di sekolah. Transisi pola pembelajaran jarak jauh ke tatap muka telah memberikan perubahan yang signifikan pada siswa sekolah menengah pertama dari sisi cara mereka mengakses informasi yang mereka butuhkan terkait pemeblajaran. Penelitian ini mencoba mengkaji pola pencarian informasi siswa pada masa transisi tersebut. Penelitian ini merupakan penelitian kualitatif dengan observasi dan wawancara kepada siswa SMPN 1 Cibatu Kab. Garut. Temuan penelitian menunukan bahwa pola pencarian informasi berdasarkan model pencarian informasi David Ellis, hanya 3 proses yang dilalui oleh siswa yakni starting, chaining, browsing. Perubahan pola kebiasaan mencari informasi melalui mesin perncari berbasis internet membuat siswa tidak melakukan pendalaman pencarian informasi. Transisi pola pembelajaran jarak jauh ke tatap muka memberikan implikasi sumber informasi berbasis jaringan internet menjadi sumber utama untuk memenuhi kebutuhan informasi di lingkungan pendidikan. Penelitian selanjutnya akan berfokus pada efektifitas pemanfaatan mesin pencari sebagai sarana belajar siswa.